Numerical modelling of the shallow reinjection and tracer transport at Nesjavellir Geothermal System, Iceland : an assessment of heat transfer and fluid flow - Gómez-Díaz, Esteban, 1993- (2020)
This thesis work was carried out in cooperation with Reykjavík Energy. The Nesjavellir geothermal power plant is the second largest in Iceland, with a district heating capacity of 300 MW and electrical generation of 120 MW. Reinjection of the excess water from the Nesjavellir geothermal plant, derived from separated water from high enthalpy wells and condensed steam, has affected the temperature of the shallow groundwater in the area. These discharges of warm water present a risk to cold water production for the power plant as well as the ecosystem in Lake Thingvellir, which is a UNESCO World Heritage Site. This study investigates the flow path of reinjected liquid and temperature of impacted groundwater for a better management of the discharge and injection in the area. A numerical model of the Nesjavellir warm wastewater re-injection zone was developed using the TOUGH2 non-isothermal flow simulator program and incorporates a 3D geological model developed with Leapfrog Geothermal modeling software. The model was calibrated against underground water temperature data measured between 1998 - 2018 from several monitoring stations located to the north of the power plant. Hydrological parameters such as porosity and permeability were further calibrated against data from a tracer test carried out in the area between 2018-2019. Both models use the Multiple Interactive Continuum (MINC) method, which is a generalization of the dual-porosity method. Compared to the single-porosity model, the MINC method better replicates the fast and strong recovery of tracers found in the monitoring stations. The temperature model showed acceptable results that match the temperature field. While the tracer model closely matches the overall tracer return in some wells, the model underestimates tracer returns in others. However, the model reproduces the overall trend, with similar tracer arrival and concentration peaks for monitoring stations located over main structures acting as permeable channels. Two future scenarios were simulated ...